Gestión social y su influencia en la calidad de vida de las asociaciones agroproductivas de Fundación Maquita en la ciudad de Portoviejo - Cedeño Ordoñez, Marcelo Rafael (2024)
The objective of this research work is to diagnose the social management of the Maquita Foundation to determine the influence on the quality of life of its associates. In the first phase of the research, interviews and surveys were applied to the agricultural producing partners, together with the coordinators and social managers, with the purpose of collecting information and based on the results, proposing improvement strategies for the benefit of the parties involved. The study was applied according to the sampling criteria established in three rural associations located in the cities of Calceta and Junín, which included the participation of 76 agricultural producers. In the second phase of the research, the relationship between the variables social management and quality of life was determined through Spearman's rho correlation method, which made it possible to measure the degree of incidence between both elements. In the final phase of the research, the 5w+2h matrix was implemented with the purpose of proposing strategies that contribute to overcoming the deficiencies identified in the application of management by the foundation. Where the main results showed a positive impact between the social management of the organization and the quality of life of its collaborators, but with some shortcomings that affect the efficient development of the organization's activities.